DIDACTIC REQUIREMENTS AND CONDITIONS OF DEVELOPING THE CREATIVE SKILLS OF STUDENTS FOR THE ENGINEERING PROFESSION - Eshkuvvatov Ulugbek Abdullo o’g’li (Ta'lim innovatsiyasi va integratsiyasi, 2023)
Abstract: In the article, students of higher education institutionsto the engineering professionto develop creative abilitiesfulfillment of didactic requirements and conditionsthroughformation of career-oriented creative ability in future engineersthe issue is stated.